Providing Web Based Learning Materials (GOOGLE CLASSROOM) For Teaching Essay Writing Course - Nor, Hidayah (English Education: Jurnal Tadris Bahasa Inggris, 2018)
The utilization of modern technologies in classrooms such as web based learning gives learners the opportunity to learn faster with better function and with more satisfaction from their class attendance.. The purpose of this research was to integrate the advance of technology (Google Classroom) that can be used in teaching and learning process for conveying the Essay writing materials to the students based on the syllabi of Essay Writing course to make the learners are able to write different types of essays correctly. Test, observation and documentation were analyzed qualitatively. The result of this research was to provide lecturers with interesting and effective teaching materials in enhancing the students’ understanding the essay writing. The students were expected to master in writing different types of essay related to the course materials. This research also gave additional value to the effort of increasing the quality of teaching English particularly by using web based learning (Google Classroom) in Indonesia.